Structural change(s) in Ghana: A comparison between the trade, formal and informal sectors - Bernardo Caldarola (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This paper uses the case of Ghana to unpack the role of the informal sector in the process of structural change. A structuralist view of structural change - framed as changes in the employment shares of different industries - is combined with the insight that countries strive to diversify towards more complex industries in pursuit of economic upgrading. The paper adopts and adapts the product space and complexity analytical frameworks to compare changes in the relative importance of industries across the trade, formal and informal sectors, over a ten-year period starting in 2003. To assess whether the Ghanaian labour force has moved towards more or less complex industries, the changes in relative shares of finely disaggregated industries are assessed against an employment-based industrial complexity index. The results indicate that Ghana's export and formal sectors have moved towards more complex industries, although export specialisation has moved towards export of natural resources. While exports of manufactured goods have increased, employment in formal and informal manufacturing has contracted, although, in the former case, employment has relocated towards more complex manufacturing industries. In contrast, the informal sector has moved towards less complex activities. The results stress on the need to align the productive capabilities of the informal sector with the Ghana's productive structure in order to allow the participation of Ghanaian households to the process of structural transformation.
Keywords: J21; O14; O17; O55; 330; Structural change; industrial complexity; Ghana; employment; informality